(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Using specific antidotes for the treatment of acute poisoning that is due to drug overdose by drugs adsorption is of significant importance in physical pharmacy for the preparation of physical antidotes. Objective:The adsorption of folic acid from aqueous solution was investigated on two adsorbents (bentonite and Iraqi kaolin). Methods:The present study involves studying adsorption of folic acid on Iraqi clays (bentonite and kaolin) from aqueous solution. Adsorption isotherm of folic acid on both surfaces used obeyed Freundlich isotherm. UV- Spectrophotometric technique was used to obtain the quantities of adsorption data at different conditions of temperature. Results:The quantities adsorbed of the folic acid for bentonite and kaolin was increased at 37oC. Adsorption characteristics were described using Freundlich isotherm. The value of ?G? showed the spontaneous nature of the folic acid adsorption on both adsorbents. Conclusion:This result indicated the surface heterogeneity leading to different adsorption forces from site to site and different affinities toward drug molecules. Thermodynamic parameters have been calculated at different temperatures. The adsorption of folic acid increases with increase in temperature and positive value of ?H? indicates endothermic nature of the adsorption process. Negative values of free energy at all studied temperatures indicate that the adsorption process is spontaneous and favorable for folic acid. Positive value of entropy suggests increased randomness at the solid/solution interface. Keyword: Adsorption, folic acid, bentonite, kaolin, thermodynamic parameters.